High‐Resolution Melt as a Screening Method in Autosomal Dominant Polycystic Kidney Disease (ADPKD). Issue 4 (22nd March 2014) - Virzì, Grazia Maria; Bruson, Alice; Corradi, Valentina; Gastaldon, Fiorella; de Cal, Massimo; Donà, Marta; Cruz, Dinna N.; Clementi, Maurizio; Ronco, Claudio
<x xml:space="preserve">Abstract</x> Background Autosomal dominant polycystic kidney disease (ADPKD) is an inherited condition caused by PKD1 and PKD2 mutations. Complete analysis of both genes is typically required in each patient. In this study, we explored the utility of High‐Resolution Melt (HRM) as a tool for mutation analysis of the PKD2 gene in ADPKD families. Methods HRM is a mismatch‐detection method based on the difference of fluorescence absorbance behavior during the melting of the DNA double strand to denatured single strands in a mutant sample as compared to a reference control. Our families were previously screened by linkage analysis. Subsequently, HRM was used to characterize PKD2‐linked families. Amplicons that produced an overlapping profile sample versus wild‐type control were not further evaluated, while those amplicons with profile deviated from the control were consequently sequenced. Results We analyzed 16 PKD2‐linked families by HRM analysis. We observed ten different variations: six single‐nucleotide polymorphisms and four mutations. The mutations detected by HRM and confirmed by sequencing were as follows: 1158T>A, 2159delA, 2224C>T, and 2533C>T. In particular, the same haplotype block and nonsense mutation 2533C>T was found in 8 of 16 families, so we suggested the presence of a founder effect in our province. Conclusions We have developed a strategy for rapid mutation analysis of the PKD2 gene in ADPKD families, which utilizes an HRM‐based prescreening followed by direct sequencing of amplicons with abnormal profiles. This is a simple and good technique for PKD2 genotyping and may significantly reduce the time and cost for diagnosis in ADPKD.